Análise do desempenho entre os fundos de investimentos imobiliários e o investimento direto em imóveis - Stertz, Estefana da Silva (2016)
Economic stability after the start of the Real Plan, coupled with changes in policies and guidelines of the Brazilian real estate market, allowed the creation of new products, including securitized. This caused increased the developments in the sector, since investments in real estate to investments in shares in the capital markets, especially in this environment, the Real Estate Investment Funds (FIIs). However, after the quiet of the last decade, the housing market has not progressed in 2014, showing an increase below inflation. Therefore, the importance of conducting an analysis calculated on the financial performance of both FIIs as direct investment in real estate through IGMI-C, and the study of risk and return of such investments. In order to achieve the proposed goals, referenced indicators in finance literature were used (Sharpe Ratio, Sortino Ratio, Treynor Index, Alpha Jensen, and Modigliani and Modigliani Index) as well as the Pricing Model Assets and their regressions due to the analysis of risk and return. The data collected are classified as secondary, covered the period from January 2013 to December 2015; they were obtained through the websites of BM & FBOVESPA, FGV, the Central Bank and FIPE. As a result, it can be observed that the IGMI-C had the best performance in the sample period studied, and among the FIIs analyzed individually as well as the average of the same and the contents of the real estate market; the IGMI-C proved to be the most suitable, representing what would be the most advantageous direct investment in real estate than in shares of REITs.